1990
DOI: 10.1152/jappl.1990.69.3.822
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of aging related to outcome in the adult respiratory distress syndrome

Abstract: Thirty-nine patients with adult respiratory distress syndrome (ARDS) were enrolled in a study to identify potential age-related changes in organ system function that may help explain the apparent association between age and poor outcome in these patients. Criteria for enrollment included an arterial PO2-to-inspired O2 concentration ratio less than or equal to 200 in a clinical setting consistent with ARDS. Patients were excluded if they were less than 18 yr old, had clinical manifestations of congestive heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 0 publications
4
28
0
1
Order By: Relevance
“…Although difference in ICU mortality between the thee age groups did not reach statistical significance, probably due to the small size of our age-groups, our findings are consistent with previous reports in larger ARDS cohorts showing significantly higher mortality in aged ARDS patients [36,37]. Age related declines in cardiovascular function [10], increased incidence of sepsis [38] and presence of chronic underlying health problems, have been suggested, among others, as possible explanations.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Although difference in ICU mortality between the thee age groups did not reach statistical significance, probably due to the small size of our age-groups, our findings are consistent with previous reports in larger ARDS cohorts showing significantly higher mortality in aged ARDS patients [36,37]. Age related declines in cardiovascular function [10], increased incidence of sepsis [38] and presence of chronic underlying health problems, have been suggested, among others, as possible explanations.…”
Section: Discussionsupporting
confidence: 87%
“…As per our protocol however, we were obliged to maintain the ventilatory settings selected by patients' attending physicians, which at any event reflect common practice [35]. Previous studies identified the use of lower PEEP levels in elderly patients [10,36]. In the present cohort, the similarity of ventilator settings between the three age groups may be interpreted by the comparable physiologic measurements across the age spectrum.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Tertile categorization detected useful information about the overall population that was not as evident when evaluating mean values of those variables. In general, outcome is worse with increasing age (17), patients with more severe lung injury tend to have lower PaO 2 /FiO 2 (4), and there is a direct relationship between plateau pressure and mortality (18).…”
Section: Apps: An Apgar Score For Ardsmentioning
confidence: 99%